Pengaruh Pemberian Fibroblast Growth Factor (FGF) dari Telur Ayam Terfertilisasi Terhadap Kadar Glukosa Darah Mencit Hiperglikemia - Irene Puspa Dewi; Surya Dharma; Marlina Marlina (Fakultas Farmasi Universitas Andalas, 2016)
A study on the effect of Fibroblast Growth factor (FGF) derived from fertilized chicken egg on blood glucose level in hyperglycemia mice induced by alloxan has been done. FGF taken from fertilized chicken egg white, the egg white dried with Freeze dryer method and powdered into flour. The egg powdered was tested quantitatively by ELISA (The Enzimed-Link immunosorbent assay ) method to determine the levels of FGF contained therein. And then, FGF was given to hyperglycemia mice induced alloxan. Blood glucose levels were observed periodically every week for 4 weeks after administration of FGF preparations. The results found, the levels of FGF in fertilized chicken egg white powder contained about 219 ng / L and the induction of FGF to hyperglycemia mice were able to improve blood glucose levels in mice hyperglycemia.